A novel mobiles android application for facilitating wheelchair users access to public buildings in urban environments - Saadeh Z. Sweidan; Khalid A. Darabkh; Rawan Abdalla Mohommad Afaneh (Scientific Reports)
Abstract In recent years, societies and governments worldwide have increasingly focused on addressing the rights and needs of individuals with various disabilities. Concurrently, smartphone applications (apps) have gained widespread popularity across diverse age groups. Today, there is an app available for nearly every aspect of daily life, from weather forecasts to online education and banking. Many of these apps are designed to assist people with disabilities, including those who use wheelchairs. Most apps related to wheelchair accessible buildings around the world provide only basic features like finding buildings, rating their accessibility features, and filtering search results. Even more, they usually don’t support Arabic language which may be a challenge for the users in Arabic countries. To fill this gap, we introduce WellPathJo, as an Android application with both Arabic and English interfaces that is designed to help users identify accessible public buildings in major cities. In fact, we present a complete suite of features, no other similar app offers like the ability to add new buildings, exchange experiences between users, and even provide a chatbot to response to queries. WellPathJo includes four key accessibility features: ramps, elevators, restrooms, and parking spaces. The app caters to three user types: admins, building owners, and wheelchair users. Admins oversee the overall system, building owners update information for specific buildings, and wheelchair users can use the app to find public buildings, learn about their accessibility features, and provide feedback through ratings and comments. To assess the app’s effectiveness, a survey was conducted after a one-month trial period with a group of potential users. The responses have shown general satisfaction. The chatbot was rated positively by 75%, and 80% were satisfied with community interactions. 70% felt confident using the emergency button feature. Navigation and the Arabic version of the app also received positive feedback from 85%. On the other hand, 75% rated the chatbot interface favorably, and 85% found search results accurate. Additionally, 78% felt comfortable using the app for extended periods. In conclusion, WellPathJo was well received. Looking ahead, future enhancements will incorporate artificial intelligence, support additional languages, add new accessibility features, complement new cities, and include an iOS version, among other plans.